Cholesterol Dysmetabolism in Alzheimer's Disease: A Starring Role for Astrocytes? - Erica Staurenghi; Serena Giannelli; Gabriella Testa; Barbara Sottero; Gabriella Leonarduzzi; Paola Gamba (MDPI AG, 2021)
In recent decades, the impairment of cholesterol metabolism in the pathogenesis of Alzheimer's disease (AD) has been intensively investigated, and it has been recognized to affect amyloid β (Aβ) production and clearance, tau phosphorylation, neuroinflammation and degeneration. In particular, the key role of cholesterol oxidation products, named oxysterols, has emerged. Brain cholesterol metabolism is independent from that of peripheral tissues and it must be preserved in order to guarantee cerebral functions. Among the cells that help maintain brain cholesterol homeostasis, astrocytes play a starring role since they deliver de novo synthesized cholesterol to neurons. In addition, other physiological roles of astrocytes are to modulate synaptic transmission and plasticity and support neurons providing energy. In the AD brain, astrocytes undergo significant morphological and functional changes that contribute to AD onset and development. However, the extent of this contribution and the role played by oxysterols are still unclear. Here we review the current understanding of the physiological role exerted by astrocytes in the brain and their contribution to AD pathogenesis. In particular, we focus on the impact of cholesterol dysmetabolism on astrocyte functions suggesting new potential approaches to develop therapeutic strategies aimed at counteracting AD development.